Is Docetaxel the Main Therapy for Lung Metastasis in Granular Cell Tumors? - Heru Sigit Pramono; Ana Rima Setijadi; Yusup Subagio Sutanto; Brian Wasita (Faculty of Medicine Universitas Airlangga, 2023)
Introduction: A granular cell tumor is a rare neoplasm originating from mesenchymal tissue. Malignant granular cell tumors have a poor prognosis. The lung is one of the target organs for metastatic malignant granular cell tumors. The number of rare cases makes managing metastatic malignant granular cell tumors unknown. Case: A 19-year-old male complained of shortness of breath for two months. A liver nodule biopsy revealed poorly differentiated carcinoma metastases. Histopathology of the left manus and frontal masses found granular cell tumors”negative immunohistochemistry on S-100 and myogenin. Ki-67 obtained a value of 5%. An X-ray and contrast multislice computerized tomography (MSCT) scan showed multiple metastatic nodules. Right bronchial biopsy forceps revealed a metastatic granular cell tumor. The patient was given docetaxel for six cycles. During the post-administration of docetaxel, the patient experienced clinical and radiological improvement. Conclusion: Until 2016, only three case reports of S-100 negative granular cell tumors existed. A negative S-100 test does not rule out the diagnosis of granular cell tumors. Malignant lesions are more common in males, as in this case. The number of rare cases means that management cannot be determined. Reports of similar cases show patients surviving up to 11 years with docetaxel administration. The patient in this study has survived for one year and is complaint-free.